Analysis of Continuous Auditing Implementation in The Public Sector: A Case Study of the Ministry of ABC - Sri Suharto; Heny Kurniawati (Universitas KH. Abdul Chalim Mojokerto, 2024)
Public organizations face challenges in budget management accountability, including the continuously increasing budget, recurring findings of budget management non-compliance, dispersed work units across Indonesia, and limited auditor human resources. This case study aims to provide an understanding of the effectiveness of continuous auditing implementation in the public sector, particularly within the Ministry of ABC. The Ministry of ABC plays a strategic role in governance, involving functions such as planning, fund allocation, monitoring, and controlling development planning. From the budget management perspective, it is not excessively large but has complexity due to managing funds sourced from pure domestic currency and foreign loans and grants. To achieve the research objectives, we conducted interviews with auditors, made observations, and reviewed documents related to the implementation of continuous auditing in the organization. The research findings indicate that the implementation of continuous auditing in the ministry has largely reached level IV (continuous auditing) for five criteria, namely data access and retrieval, automated auditing and analysis methods, internal audit unit, audit objectives and human resources, and there is one criterion at level III (structure analysis), namely the audit approach and monitoring. Level IV indicates that the organization's internal control has been institutionalized into continuous auditing by conducting continuous testing and reporting internal control. Internal audit has used advanced analytical methods, developed audit plans, and dashboards for visualizing the results of data analysis and trends. Based on the research results, it is expected to provide lessons learned to enhance budget management accountability and best practices for other government agencies to adopt continuous auditing methodologies.